Classification of cognitive performance in bipolar disorder. Issue 5 (3rd September 2017) - Sparding, Timea; Silander, Katja; Pålsson, Erik; Östlind, Josefin; Ekman, Carl Johan; Sellgren, Carl M.; Joas, Erik; Hansen, Stefan; Landén, Mikael
ABSTRACT: Objective: To understand the etiology of cognitive impairment associated with bipolar disorder, we need to clarify potential heterogeneity in cognitive functioning. To this end, we used multivariate techniques to study if the correlation structure of cognitive abilities differs between persons with bipolar disorder and controls. Method: Clinically stable patients with bipolar disorder (type I: n  = 64; type II: n  = 44) and healthy controls ( n  = 86) were assessed with a wide range of cognitive tests measuring executive function, speed, memory, and verbal skills. Data were analysed with multivariate techniques. Results: A distinct subgroup (∼30%) could be identified that performed significantly poorer on tests concerning memory function. This cognitive phenotype subgroup did not differ from the majority of bipolar disorder patients with respect to other demographic or clinical characteristics. Conclusions: Whereas the majority of patients performed similar to controls, a subgroup of patients with bipolar disorder differed substantially from healthy controls in the correlation pattern of low-level cognitive abilities. This suggests that cognitive impairment is not a general trait in bipolar disorder but characteristic of a cognitive subgroup. This has important clinical implications for cognitive rehabilitation and remediation.